Heart rate response to post-learning stress predicts memory consolidation - Larra, Mauro F.; Schulz, André; Schilling, Thomas M.; Ferreira de Sá, Diana S.; Best, Daniel; Kozik, Bartlomiej; Schächinger, Hartmut (Neurobiology of learning and memory, 2014)
•Cold Pressor Tests were administered shortly after learning of emotional faces.•The stress induced heart rate response was found to predict 24h delayed identity memory.•Thus, endogenous beta-adrenergic activation enhances memory consolidation. Stressful experiences are often well remembered, an effect that has been explained by beta-adrenergic influences on memory consolidation. Here, we studied the impact of stress induced heart rate (HR) responses on memory consolidation in a post-learning stress paradigm. 206 male and female participants saw 52 happy and angry faces immediately before being exposed to the Cold Pressor Test or a non-stressful control procedure. Memory for the faces and their respective expression was tested twice, after 30min and on the next day. High HR responders (in comparison to low HR responders as well as to the non-stressful control group) showed enhanced recognition memory one day after learning. Our results show that beta-adrenergic activation elicited shortly after learning enhances memory consolidation and that the stress induced HR response is a predictor for this effect.